Comparing physical activity of Malaysian Malay men and women before, during, and after Ramadan - Soh, Kim Geok; Yusof, Aminuddin; Abdullah, Nur Surayyah Madhubala; Soh, Kim Lam; Ong, Swee Leong (Universiti Putra Malaysia Press, 2013)
The aims of this research were to investigate whether there is any difference in the physical activity levels between Malay Muslim men (Muslim) and Malay Muslim women (Muslimah) at Universiti Putra Malaysia (UPM) before, during, and after the month of Ramadan, and also to determine the factors restricting their involvement in physical activities. Fifty-three UPM Malay Muslim male staff and fifty-four UPM Malay Muslim female staff participated in the research. The Yamex-Digi walker CW700 pedometer was used to measure the physical activity level of the staff for four consecutive days. Results showed that there was no significant difference in the physical activity levels of the Malay Muslim and Muslimah in UPM before, during, and after the month of Ramadan. The reported t-test results comparing the two genders before, during, and after the month of Ramadan were f=0.003, p<0.96, f=1.047, p<0.31, and f=3.106, p<0.08, respectively. It was reported that the lack of self motivation/laziness played the most important role in restricting the involvements of both genders in the physical activities.